The Effect Of Human Relation And Environmental Conditions On Employees Work Ethic - Suryadin Yedon; Mistar Kaharudin Rian (Jambura Science of Management, 2021)
The purpose of this study was to determine and analyze the effect of human relations and working environment conditions partially and simultaneously on the work ethics of Woha's Procurement Service Unit employees. The research method used is associative with a quantitative approach. The sampling technique used was saturated sampling so that the entire population was used as a sample in this study as many as 53 respondents, the research instrument was a questionnaire or questionnaire. Data analysis techniques used are the validity and reliability test, the classic assumption test, multiple linear regression analysis, the coefficient of detemination, the t test and the F test. Based on the results of statistical tests conducted partially human relations have a positive and significant effect on the work ethic of Woha's Procurement Service Unit employees. Based on the results of statistical tests conducted partially human relations have a positive and significant effect on the work ethic of Woha's Procurement Service Unit employees. While the work environment conditions have a negative and not significant effect on the work ethics of Woha's Procurement Service Unit employees. Simultaneously, human relations variables and work environment conditions significantly influence the work ethics of Woha's Procurement Service Unit employees.